Mitochondrial dysfunction and neurodegeneration in multiple sclerosis - Kimmy eSu; Kimmy eSu; Dennis eBourdette; Dennis eBourdette; Michael eForte (Frontiers in Physiology, 2013)
Multiple sclerosis (MS) has traditionally been considered an autoimmune inflammatory disorder leading to demyelination and clinical debilitation as evidenced by our current standard anti-inflammatory and immunosuppressive treatment regimens. While these approaches do control the frequency of clinical relapses, they do not prevent the progressive functional decline that plagues many people with MS. Many avenues of research indicate that a neurodegenerative process may also play a significant role in MS from the early stages of disease, and one of the current hypotheses identifies mitochondrial dysfunction as a key contributing mechanism. We have hypothesized that pathological permeability transition pore opening mediated by reactive oxygen species and calcium dysregulation is central to mitochondrial dysfunction and neurodegeneration in MS. This focused review highlights recent evidence supporting this hypothesis, with particular emphasis on our in vitro and in vivo work with the mitochondria-targeted redox enzyme p66ShcA.